2008
DOI: 10.1016/j.neucom.2007.08.029
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive stereo basis method for convolutive blind audio source separation

Abstract: We consider the problem of convolutive blind source separation of stereo mixtures, where a pair of microphones records mixtures of sound sources that are convolved with the impulse response between each source and sensor. We propose an Adaptive Stereo Basis (ASB) source separation method for such convolutive mixtures, using an adaptive transform basis which is learned from the stereo mixture pair.The stereo basis vector pairs of the transform are grouped according to the estimated relative delay between the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…A number of studies have been performed to assess the subjective quality of certain source separation schemes [10], [11], [12], [13], [14], [15], [16], [17]. Most studies consider either a single criterion, such as overall quality [10], [14], [15], preference [13, p. 138] or musical noise salience [12], [18], or a set of criteria restricted to speech [11], [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have been performed to assess the subjective quality of certain source separation schemes [10], [11], [12], [13], [14], [15], [16], [17]. Most studies consider either a single criterion, such as overall quality [10], [14], [15], preference [13, p. 138] or musical noise salience [12], [18], or a set of criteria restricted to speech [11], [16].…”
mentioning
confidence: 99%
“…Independent Component Analysis (ICA) in [13], time-frequency masking in [10] or simulated separation in [16], and a narrow range of sound material, e.g. male speech in [14], [17] or isolated notes from a single musical instrument in [15]. The resulting scores can hence not be compared due to the lack of a common absolute reference.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Double sparsity refers to seeking a sparse decomposition and a dictionary D = AB such that the atoms in A are sparse over the fixed dictionary B, such as Wavelets or the discrete cosine transform (DCT). Also, in previous results in [17], it was found that dictionary atoms learned from speech signals with a sparse coding method based on ICA (SC-ICA) [18], are localized in time and frequency. This appears to suggest that for certain types of signals (e.g.…”
Section: A Motivationmentioning
confidence: 99%
“…Each row of W is a 1 × M un-mixing vector w i related to one of extracted signals. Many strategies have been used for BSS [6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. One of them is projection pursuit [6] that is based on the central limit theorem (CLT) [7].…”
Section: Introductionmentioning
confidence: 99%